1998
DOI: 10.1080/002075498193264
|View full text |Cite
|
Sign up to set email alerts
|

The effect of autocorrelated demand in JIT production systems

Abstract: As a system of production planning and inventory control for multi-stage production inventory systems, this paper deals with the Kanban system in the just-intime (JIT) concept. In this paper, the autocorrelation of demand is considered as an important factor a ecting the performance of the Kanban system. Mathematical models of a Kanban system and its modi® ed system are developed as sequential and concurrent ordering systems, respectively. By means of simulation experiments, the e ects of the autocorrelation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…These conclusions are also shared by Takahashi and Nakamura [51], Altiok and Melamed [52] and Pereira et al [53], who found that both positive and negative Corr(A) and Corr(S) have a negative impact on the performance of serial production lines.…”
Section: Auto-correlated Processessupporting
confidence: 58%
“…These conclusions are also shared by Takahashi and Nakamura [51], Altiok and Melamed [52] and Pereira et al [53], who found that both positive and negative Corr(A) and Corr(S) have a negative impact on the performance of serial production lines.…”
Section: Auto-correlated Processessupporting
confidence: 58%
“…They introduce autocorrelation by means of TES (Transform-Expand-Sample) processes and their results alert on the potential losses on accuracy that might be derived from an inadequate use of independence assumption. Takahashi and Nakamura (1998) studied the case of Just-In-Time systems achieving similar conclusions. Balcioglu et al (2007) provide an approximate solution for the mean waiting times when autocorrelation is present in time to failure time series.…”
Section: Introductionmentioning
confidence: 69%
“…Livny et al (1993) demonstrate that autocorrelation in service or inter-arrival times may severely affect the queue lengths and consequently waiting time distribution of a system. Takahashi and Nakamura (1998) analyze a production system controlled by Kanban cards with concurrent and sequential ordering processes. They demonstrate that correlated demand arrivals can have significant impact on the WIP inventories and on the expected waiting time of the products.…”
Section: Impact Of Correlation On the Performance Of Queuing And Manumentioning
confidence: 99%